ANALYSIS OF THE INFLUENCE OF SUPPLY CHAIN MANAGEMENT ON COMPANY PERFORMANCE: STUDY ON CATFISH FARMING COMMUNITY OF RED WATER SYSTEM AND BIOFLOC IN WONOGIRI - Salim Ukhrowi (Journal of Management and Islamic Finance, 2021)
The aim of this study is to analyze the factors that influence the performance of the company's supply chain management with a case study of the catfish farming community red water system and bioflok in Wonogiri 2021. This study used a questionnaire as a medium in collecting data which was then analyzed by multiple regression in SPSS 25.0. Three variables consisting of information sharing, long term relationship, and cooperation, is considered to have an influence on the performance of the company's supply chain management. The results showed that information sharing and cooperation significantly influence the performance of the company's supply chain management, while long term relationship has no significant effect. Based on the results of this study, it can be concluded that the factors considered by the catfish farming community red water system and bioflok in Wonogiri, to provide better company performance are information sharing and cooperation. There are clarity and trust in information sharing and cooperation between breeders, farmers, and collectors, so the quality of the information sharing and cooperation are obtained allows farmers to run the business well. Therefore, to improve the performance of enterprise supply chain management, the catfish farming community need to optimize long-term relationship. This is due to the lack of trust that exists between the breeders, farmers, and collectors due to prices that often change; this causes farmers to often look for new breeders or collectors in the hope of not harming the farmers.Â